A proteção da biodiversidade latino-americana frente aos direitos de propriedade intelectual sob o modelo TRIPs: alternativas e divergências - Vieira, Vinicius Garcia (2009)
The Latin America, the richest continent in the planet's biodiversity, has been subject to expropriation by multinational corporations seeking access to plants and animals or knowledge related to biodiversity, produced by indigenous peoples or traditional communities, which will give support to the scientific findings used by large industries in the production of medicines, cosmetics and a wide variety of products available in the market, for wich the industries claimed intellectual property rights, with the exclusion of traditional populations. In this scenario, there are overlaps between The CBD and TRIPs Agreement in multilateral settings, where the possibility of protecting biodiversity shares space with the same tendency to your merchandization. Although the The CBD and TRIPs Agreement structure different international issues, this norms interact from the granting of intellectual property rights on biodiversity products. Because of this, the research aims to comprehend the extent to which intellectual property rights under the WTO model, notably patents, impact on biodiversity protection by the Latin American countries. Investigates the multilateral regulation of biodiversity protection and intellectual property with the central analysis, respectively, in the CBD and TRIPs. Then, the structures of the multilateral system are confronted with a sui generis system, in order to find out if they are alternatives to protect biodiversity in Latin America. Thus, was possible to conclude that the Latin American countries have their possibilities to care of the biodiversity limited by international regime of intellectual property, which allows private ownership of biodiversity in the form of biotechnologies. This provides two contrary ways: to maintain the international regime of intellectual property that ensures the trade of bio-merchandise with patents, or to structure a regulatory framework to care of biodiversity, in the Conference of the Parties to the CBD and negotiations in the Council for TRIPs. However, the strong opposition of the North countries to the interests of Latin American countries leads to investigate a sui generis system, to articulate a unified position in Latin America for the international confrontation and have for basis the guarantee of rights to the traditional peoples on their traditional knowledge.